Proyectos de aprendizaje y el desarrollo integral de los niños de la institución educativa inicial N°672 San Juan Baustista 2024 - Gonzales Celis, Adriana Valentina (2025)
The objective of this research was to determine the relationship between learning projects and the integral development of children at the Initial Educational Institution N°672 San Juan Bautista in 2024. The adopted approach was quantitative, with a non-experimental, relational research design, using a correlational cross-sectional design. The study population consisted of 48 children from the institution. For data collection, the observation technique was used, employing a guide specifically designed for this purpose, whose validity was supported by a team of experts in the field. The results obtained support the research hypothesis and show a Spearman correlation coefficient of 0,754, indicating a moderate positive relationship between the two variables. Additionally, the bilateral significance value of 0,05 demonstrates that the finding is statistically significant at the 0,05 level. In conclusion, it is established that learning projects have a significant relationship with the integral development of children at the Initial Educational Institution N°672 San Juan Bautista, allowing for the rejection of the null hypothesis.